# calculate-0-1-e-2t-ln-1-t-dt-

Question Number 65925 by mathmax by abdo last updated on 05/Aug/19
$${calculate}\:\int_{\mathrm{0}} ^{\mathrm{1}} {e}^{−\mathrm{2}{t}} {ln}\left(\mathrm{1}−{t}\right){dt} \\$$
Commented by mathmax by abdo last updated on 07/Aug/19
$${let}\:{I}\:=\int_{\mathrm{0}} ^{\mathrm{1}} \:{e}^{−\mathrm{2}{t}} {ln}\left(\mathrm{1}−{t}\right){dt}\:\:{we}\:{have}\:\:{ln}^{'} \left(\mathrm{1}−{t}\right)\:=\frac{−\mathrm{1}}{\mathrm{1}−{t}}=−\sum_{{n}=\mathrm{0}} ^{\infty} \:{t}^{{n}} \: \\$$$${for}\:\mid{t}\mid<\mathrm{1}\:\Rightarrow{ln}\left(\mathrm{1}−{t}\right)\:=−\sum_{{n}=\mathrm{0}} ^{\infty} \:\frac{{t}^{{n}+\mathrm{1}} }{{n}+\mathrm{1}}\:=−\sum_{{n}=\mathrm{1}} ^{\infty} \:\frac{{t}^{{n}} }{{n}}\:\Rightarrow \\$$$${I}\:=−\int_{\mathrm{0}} ^{\mathrm{1}} \:{e}^{−\mathrm{2}{t}} \left(\sum_{{n}=\mathrm{1}} ^{\infty} \:\frac{{t}^{{n}} }{{n}}\right){dt}\:=−\sum_{{n}=\mathrm{1}} ^{\infty} \:\frac{\mathrm{1}}{{n}}\:\int_{\mathrm{0}} ^{\mathrm{1}} \:{t}^{{n}} {e}^{−\mathrm{2}{t}} {dt} \\$$$${let}\:{A}_{{n}} =\int_{\mathrm{0}} ^{\mathrm{1}} \:{t}^{{n}} \:{e}^{−\mathrm{2}{t}} {dt}\:\:\:{by}\:{psrts}\:{u}^{'} \:={t}^{{n}} \:{and}\:{v}={e}^{−\mathrm{2}{t}} \\$$$${A}_{{n}} =\left[\frac{\mathrm{1}}{{n}+\mathrm{1}}{t}^{{n}+\mathrm{1}} {e}^{−\mathrm{2}{t}} \right]_{\mathrm{0}} ^{\mathrm{1}} −\int_{\mathrm{0}} ^{\mathrm{1}} \frac{{t}^{{n}+\mathrm{1}} }{{n}+\mathrm{1}}\left(−\mathrm{2}\right){e}^{−\mathrm{2}{t}} \:{dt} \\$$$$=\frac{{e}^{−\mathrm{2}} }{{n}+\mathrm{1}}\:+\frac{\mathrm{2}}{{n}+\mathrm{1}}\:\int_{\mathrm{0}} ^{\mathrm{1}} \:{t}^{{n}+\mathrm{1}} {e}^{−\mathrm{2}{t}} \:{dt}\Rightarrow\left({n}+\mathrm{1}\right){A}_{{n}} ={e}^{−\mathrm{2}} +\mathrm{2}{A}_{{n}+\mathrm{1}} \:\Rightarrow \\$$$$\mathrm{2}{A}_{{n}+\mathrm{1}} =\left({n}+\mathrm{1}\right){A}_{{n}} −{e}^{−\mathrm{2}} \:\Rightarrow{A}_{{n}+\mathrm{1}} =\frac{\left({n}+\mathrm{1}\right)}{\mathrm{2}}{A}_{{n}} −\frac{{e}^{−\mathrm{2}} }{\mathrm{2}}\:\Rightarrow \\$$$${A}_{{n}} =\frac{{n}}{\mathrm{2}}{A}_{{n}−\mathrm{1}} −\frac{{e}^{−\mathrm{2}} }{\mathrm{2}}\:\:\:{let}\:\:{V}_{{n}} =\mathrm{2}\frac{{A}_{{n}} }{{n}!}\:\Rightarrow \\$$$${V}_{{n}+\mathrm{1}} −{V}_{{n}} =\mathrm{2}\frac{{A}_{{n}+\mathrm{1}} }{\left({n}+\mathrm{1}\right)!}−\mathrm{2}\frac{{A}_{{n}} }{{n}!}\:=\mathrm{2}\frac{\left({n}+\mathrm{1}\right){A}_{{n}} }{\mathrm{2}\left({n}+\mathrm{1}\right)!}−\mathrm{2}\frac{{e}^{−\mathrm{2}} }{\mathrm{2}}−\mathrm{2}\frac{{A}_{{n}} }{{n}!} \\$$$$=\frac{{A}_{{n}} }{{n}!}−\mathrm{2}\frac{{A}_{{n}} }{{n}!}\:−{e}^{−\mathrm{2}} \:=−\frac{\mathrm{1}}{{n}!}{A}_{{n}} −{e}^{−\mathrm{2}} \:\Rightarrow\sum_{{k}=\mathrm{0}} ^{{n}−\mathrm{1}} \left({V}_{{k}+\mathrm{1}} −{V}_{{k}} \right) \\$$$$=−\sum_{{k}=\mathrm{0}} ^{{n}−\mathrm{1}} \frac{{A}_{{k}} }{{k}!}−{ne}^{−\mathrm{2}} \:\:\Rightarrow{V}_{{n}} −{V}_{\mathrm{0}} =−\sum_{{k}=\mathrm{0}} ^{{n}−\mathrm{1}} \:\frac{{A}_{{k}} }{{k}!}\:−{ne}^{−\mathrm{2}} \:\Rightarrow \\$$$${V}_{{n}} ={V}_{\mathrm{0}} −{ne}^{−\mathrm{2}} −\sum_{{k}=\mathrm{0}} ^{{n}−\mathrm{1}} \:\frac{{A}_{{k}} }{{k}!}\:\:…{be}\:{continued}… \\$$
Commented by mathmax by abdo last updated on 07/Aug/19
$${at}\:{form}\:{of}\:{serie}\:\:{we}\:{have}\:{e}^{−\mathrm{2}{t}} \:=\sum_{{n}=\mathrm{0}} ^{\infty} \:\frac{\left(−\mathrm{2}{t}\right)^{{n}} }{{n}!} \\$$$${and}\:{ln}\left(\mathrm{1}−{t}\right)\:=−\sum_{{n}=\mathrm{1}} ^{\infty} \:\frac{{t}^{{n}} }{{n}}\:\Rightarrow{e}^{−\mathrm{2}{t}} {ln}\left(\mathrm{1}−{t}\right) \\$$$$=−\left(\sum_{{n}=\mathrm{0}} ^{\infty} \:\frac{\left(−\mathrm{2}\right)^{{n}} {t}^{{n}} }{{n}!}\right)\left(\sum_{{n}=\mathrm{1}} ^{\infty} \:\frac{{t}^{{n}} }{{n}}\right)\:=−\left(\mathrm{1}+\sum_{{n}=\mathrm{1}} ^{\infty} \:\frac{\left(−\mathrm{2}\right)^{{n}} {t}^{{n}} }{{n}!}\right)\sum_{{n}=\mathrm{1}} ^{\infty} \:\frac{{t}^{{n}} }{{n}} \\$$$$=−\sum_{{n}=\mathrm{1}} ^{\infty} \:\frac{{t}^{{n}} }{{n}}\:−\left(\sum_{{n}=\mathrm{1}} ^{\infty} \:\frac{\left(−\mathrm{2}\right)^{{n}} {t}^{{n}} }{{n}!}\right)\left(\sum_{{n}=\mathrm{1}} ^{\infty} \:\frac{{t}^{{n}} }{{n}}\right) \\$$$$={ln}\left(\mathrm{1}−{t}\right)−\sum_{{n}=\mathrm{1}} ^{\infty} \:{c}_{{n}} {t}^{{n}} \:\:\:\:{with}\:{c}_{{n}} =\sum_{{i}+{j}=\mathrm{1}} {a}_{{i}} {b}_{{j}} \:=\sum_{{i}=\mathrm{1}} ^{{n}−\mathrm{1}} {a}_{{i}} {b}_{{n}−{i}} \\$$$$=\sum_{{i}=\mathrm{1}} ^{{n}−\mathrm{1}} \:\frac{\left(−\mathrm{2}\right)^{{i}} }{{i}!}\frac{\mathrm{1}}{{n}−{i}}\:\Rightarrow \\$$$${e}^{−\mathrm{2}{t}} {ln}\left(\mathrm{1}−{t}\right)\:={ln}\left(\mathrm{1}−{t}\right)−\sum_{{n}=\mathrm{1}} ^{\infty} \left(\sum_{{i}=\mathrm{1}} ^{{n}−\mathrm{1}} \:\frac{\left(−\mathrm{2}\right)^{{i}} }{\left({n}−{i}\right){i}!}\right){t}^{{n}} \:\Rightarrow \\$$$$\int_{\mathrm{0}} ^{\mathrm{1}} \:{e}^{−\mathrm{2}{t}} {ln}\left(\mathrm{1}−{t}\right){dt}\:=\int_{\mathrm{0}} ^{\mathrm{1}} {ln}\left(\mathrm{1}−{t}\right){dt}\:−\sum_{{n}=\mathrm{1}} ^{\infty} \left(\sum_{{i}=\mathrm{1}} ^{{n}−\mathrm{1}} \frac{\left(−\mathrm{2}\right)^{{i}} }{\left({n}−{i}\right){i}!}\right)\frac{\mathrm{1}}{{n}+\mathrm{1}} \\$$$$\int_{\mathrm{0}} ^{\mathrm{1}} {ln}\left(\mathrm{1}−{t}\right){dt}\:=_{\mathrm{1}−{t}\:={u}} \:\:\:\:−\int_{\mathrm{0}} ^{\mathrm{1}} {ln}\left({u}\right)\left(−{du}\right)\:=\int_{\mathrm{0}} ^{\mathrm{1}} {ln}\left({u}\right){du} \\$$$$=\left[{ulnu}−{u}\right]_{\mathrm{0}} ^{\mathrm{1}} \:=−\mathrm{1}\:\Rightarrow \\$$$$\int_{\mathrm{0}} ^{\mathrm{1}} {ln}\left(\mathrm{1}−{t}\right){dt}\:=−\mathrm{1}−\sum_{{n}=\mathrm{1}} ^{\infty} \:\frac{\mathrm{1}}{{n}+\mathrm{1}}\left(\sum_{{i}=\mathrm{1}} ^{{n}−\mathrm{1}} \:\frac{\left(−\mathrm{2}\right)^{{i}} }{\left({n}−{i}\right){i}!}\right) \\$$
Commented by mathmax by abdo last updated on 07/Aug/19
$$\int_{\mathrm{0}} ^{\mathrm{1}} \:{e}^{−\mathrm{2}{t}} {ln}\left(\mathrm{1}−{t}\right){dt}\:=−\mathrm{1}−…. \\$$